Allogeneic CAR-engineered cellular therapy for relapsed and refractory large B cell lymphoma: a systematic review and meta-analysis - Biederstädt, Alexander; Bassermann, Florian; Hecker, Judith S. (Frontiers in Immunology, 2025)
IntroductionRelapsed/refractory (r/r) large B-cell lymphoma (LBCL) remains a difficult-to-treat disease with limited treatment options and high unmet clinical need, necessitating the development of new therapies with greater potency and broader applicability. While autologous chimeric antigen receptor (CAR)-T cell therapies have transformed the treatment landscape, 60–65% of patients receiving these therapies eventually relapse, underscoring the need for improved approaches. Allogeneic CAR-T and CAR-NK cell therapies have recently emerged as promising alternatives, offering the potential to shorten manufacturing times, reduce costs, and expand access to a broader patient population. This systematic review and meta-analysis compiles the currently available clinical trial data on the efficacy and safety of these novel therapies in adult patients with r/r LBCL.MethodsA systematic search of MEDLINE, EMBASE, Web of Science, and the Cochrane Central Register of Controlled Trials was conducted for studies published up to January 12, 2025, involving allogeneic CAR-T and CAR-NK cell therapies in R/R LBCL. The primary outcomes assessed were the best overall response rate (bORR) and best complete response rate (bCRR) at any time point. Secondary outcomes included rates of grade 1-2 and grade 3+ cytokine release syndrome (CRS), grade 1-2 and grade 3+ immune effector cell-associated neurotoxicity syndrome (ICANS), grade 1-2 and grade 3+ infections and incidence of graft-versus-host disease (GvHD).ResultsNineteen studies met the inclusion and exclusion criteria, encompassing 334 patients (155 CAR-NK; 179 CAR-T) evaluable for safety and 235 patients evaluable for response (77 CAR-NK; 158 CAR-T). The pooled estimates for the best overall response rate (bORR) and the best complete response rate (bCRR) were 52.5% [95% CI, 41.0-63.9] and 32.8% [95% CI, 24.2-42.0], respectively. Safety analysis revealed very low incidences of grade 3+ CRS (0.04% [95% CI 0.00-0.49]) or grade 3+ ICANS (0.64% [95% CI 0.01-2.23]) and only one occurrence of a GvH-like reaction across 334 infused patients enrolled in the included studies, highlighting the remarkable safety profile of CAR-engineered “off-the-shelf” allogeneic approaches. The estimated overall incidence of low-grade CRS was 30% [95% CI, 14-48], while the estimated overall incidence of low-grade ICANS was 1% [95% CI, 0%-4%], markedly lower than current-generation autologous CAR-T cell products. The incidence of low-grade and severe infections was 25% [95% CI 14-36%) (n=252) and 7% [95% CI 2-14%] (n=291), respectively.DiscussionTogether, allogeneic CAR-T and CAR-NK cell therapies demonstrate encouraging efficacy in heavily pretreated patients with r/r LBCL. Coupled with their favorable safety profiles and the potential for off-the-shelf availability, allogeneic cell therapies hold great promise to broaden the reach of live cell-based treatments, delivering impactful results to a wider patient population in the coming years.